The Influence of Consuming Honey on The Eating Frequency of Children Under Five Years (3-5 Years) - Asti Ratnaningrum; Siswi Wulandari (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: Children under five (0-5 years) have a very high level of brain plasticity so they will be more open to learning and enrichment processes. A study in Jakarta found that preschool children aged 4-6 years have a prevalence of eating difficulties of 33.6% and most of them (79.2 have lasted more than 3 months. Purpose: To determine the influence of consuming honey on eating frequency in children aged 3-5 years. Method: This pre-experimental study used one group pretest-posttest design. This study involved 34 children aged 3-5 years determined using the simple random sampling technique. The variable measured was the consumption of honey as the independent variable, while the dependent variable was the frequency of eating before and after consuming honey. The statistical test used in this study was the Wilcoxon statistical test with a 95% confidence level (? = 0.05). The Statistic Analyses used to SPSS V.26. Results: The results showed that 26 children (76.5%) ate less than three times a day before consuming honey and 18 children (52.9%) have a frequency of eating more than three times a day after consuming honey.. The result of the bivariate test was 0.000 which is lower than 0.05. Conclusion: Consuming honey influence the frequency of eating of children aged 3-5 years. It is expected that the results of this study can enrich knowledge on the benefits of honey so that respondents can better understand and apply it at home to their children.